The Ideological Sources of Religious Leadership in Ukrainian Cultural Space - Irina Lomachinska; Svitlana Khrypko; Ganna Iatsenko (Cхід, 2019)
The urgency of a problem is determined by the strengthening influence of religious leadership on social and political processes in Ukrainian society. The religious leadership is predominantly considered in political context (as the juxtaposition of political leadership in forms and means of power access) and structural context (as being the main factor of a church structure establishment) in modern scientific thought. Among the theological thought representatives an idea of religious leadership is followed in a theological doctrine of ministry as spiritual mentorship. Simultaneously, an issue of spiritual and cultural activity of the Orthodox religious leadership has not been an object of active scientific study yet; hence a primary aim of the article is to determine the sources of a leadership’s idea in national religious and cultural traditions. A sense of religious leadership as a sophisticated institutional structure was specified in the process of an issue analysis thus identified the development directions of national religious area as well as national social and cultural space. An article highlights that the Orthodox clergy, predominantly monkhood which combined an idea of ascetic feat with hectic social activity have formed Ukrainian archetypal image of religious leadership. The article proves that an idea of the Orthodox religious leadership has been formed on the patristic tradition basis and has been reflected in the following functions: an ideological function, a missionary function, a valued-based function, a ritual function, an integrational function. A religious leader always carries some religious ideology, expressed in a system of moral and social values; therefore he forms an ideal image that is the most relevant to a particular historical period. A religious leader’s archetype is created in a sacral sphere, consequently, in contrast to a political leader; he is protected from radical ideological audits and saves the dominant influence on social consciousness